PERUBAHAN WUJUD DAN MAKNA BELIS DALAM PERKAWINAN ADAT BAJAWA BOBA - Maria Elfrida Deke; Yohanes Bahari; Izhar Salim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aims to describe changes in form, changes in meaning, and the causes of changes Belis in Bajawa Boba traditional marriages in Banda Sari Village, Air Upas District. The method used is a qualitative method with a phenomenological approach. The results showed that the form of Belis in the Bajawa Boba traditional marriage has changed in payment from the livestock become to money. But, the meaning of Belis itself in the Bajawa Boba traditional marriage has not changed even though the payment was replaced to money form. Belis is still seen as a sign of gratitude to the parents of the girl, an attorney moving or increasing the name of the fam (family) from man to woman, the media to strengthen friendly relations, and respect for woman's families by maintaining attitudes and behavior. The Factors causing of change form on Belis in Bajawa Boba traditional marriages are internal and external factors. The Internal factors include increase population and opposition in society. While external factors include the physical environment and other people's culture. The orientation in the future for the better, indirectly persuade a factor in changing on Belis payments. Keywords: Change in Form and Meaning of Belis, Bajawa Boba Traditional Marriage